Feasibility study of FFPP thermoplastic lining for concrete pipeline rehabilitation: a case study - Dongmin Xi; Yonggui Yan; Kebing Shi; Houming Ni; Mohammadamin Azimi (Urban Lifeline)
Abstract This study investigates the feasibility and efficacy of Flexible Fiber-reinforced Polypropylene (FFPP) thermoplastic lining technology for the rehabilitation of concrete pipelines, specifically focusing on BONNA pipes. A custom-built test bench, featuring a 2-m high platform and multiple 90° bends, was designed to simulate the impact of pipe gallery space, adaptability and material accessibility of bent pipes, and cooling issues of long-distance dragging of materials. The simulation process utilizes a modified polyvinyl chloride (PVC) liner with unique thermomechanical properties. The liner, folded into an "H" shape, is mechanically inserted into the host pipe using a 2-ton winch and pulley system. During insertion, continuous high-temperature steam injection softens the material, facilitating expansion and conformity to the pipe's internal surface. Subsequently, cold air application rigidifies the liner below 60 °C while maintaining pressure, ensuring structural integrity and adherence to the pipe wall. Results revealed that while the FFPP liner successfully navigated through confined spaces, including a 300 mm expansion joint, spatial constraints led to localized cracking defects during inflation. Traction feasibility tests using a 2-ton winch demonstrated high pulling resistance in sections with multiple bends. The liner exhibited excellent adhesion in straight pipe sections but showed significant wrinkling and poor adhesion in 90° bends. Notably, the liner demonstrated remarkable strength, withstanding internal pressures exceeding 3.3 MPa in a DN300 pipe with a 10 cm diameter intentional defect, far surpassing the on-site hydrostatic test pressure of 9 bar. This study addresses a significant gap in trenchless rehabilitation research by evaluating the FFPP thermoplastic lining technique in complex pipeline geometries, an area previously understudied. While the technique shows promise for structural reinforcement in straight pipe sections, our findings reveal that its application in complex pipeline geometries requires further refinement. The study contributes to the field of trenchless pipeline rehabilitation in several ways: (1) it provides empirical data on FFPP liner performance in multi-bend configurations and confined spaces, (2) it identifies specific challenges such as localized cracking and poor adhesion in bends, and (3) it demonstrates the liner's exceptional strength under high pressure conditions. These insights advance our understanding of FFPP technology's potential and limitations in concrete pipe repair, paving the way for future research and development in optimizing trenchless rehabilitation techniques for complex pipeline systems.